Monarch Habitat as a Component of Multifunctional Landscape Restoration Using Continuous Riparian Buffers - Semmens, Darius; Ancona, Zachary (Frontiers in Environmental Science, 2019)
Stabilizing the eastern, migratory population of monarch butterflies (Danaus plexippus) is expected to require substantial habitat restoration on agricultural land in the core breeding area of the Upper Midwestern U.S. Previous research has considered the potential to utilize marginal land for this purpose because of its low productivity, erodible soils, and high nutrient input requirements. This strategy has strong potential for restoring milkweed (Asclepias spp.), but may be limited in terms of its ability to generate additional biophysical and socioeconomic benefits for local communities. Here we explore the possibility of restoring milkweed via the creation of continuous riparian buffer strips around perennial and intermittent streams throughout the region. We use a GIS-based analysis to consider the potential of several different buffer-width scenarios to meet milkweed restoration targets. We further estimate the ability of these habitat areas to provide additional functionality in the form of crop pollination and water quality regulation across the entire region. Finally, we estimate the conservative economic value of these ecosystem services and compare it with the lost value of crops associated with each scenario. Results suggest that riparian buffers could be used to meet 10-43% of the total milkweed restoration target of 1.3 billion new stems with moderate management. The value of water quality and pollination benefits provided by buffers is estimated to exceed costs only for our smallest buffer-width scenario, with a cost-benefit ratio of 1:2.05. Larger buffer widths provide more milkweed, but costs to farmers exceed the benefits we were able to quantify. The large-scale restoration of multifunctional riparian corridors thus has the potential to add milkweed stems while also providing a variety of other valuable benefits. This suggests the potential to leverage monarch habitat restoration efforts for the benefit of a wider variety of species and a broader coalition of beneficiaries.